UUM law students no longer need to take training course - Borneo Post, (Kuching) (Borneo Post (Kuching), 2016)
Alor Setar: Students taking the degree in Law (Honours)(LLB) in Universiti Utara Malaysia (UUM) now no longer need to go through a training programme as the course has been recognised by the Legal Profession Qualifying Board of Malaysia (LPQB).